Equation of state of poly(dimethylsiloxane) melts - (:unkn) unknown (JOHN WILEY & SONS INC, 1998)
The pressure-volume-temperature (PVT) properties of three commercial samples of poly( dimethylsiloxane) are studied experimentally and theoretically in the temperature range 25-150 degrees C and for pressure to similar to 3 kbar. The Tait equation is employed to represent the data at elevated pressure. Isothermal compressibilities are computed for the three samples. The melt data are analyzed in terms of the Simha-Somcynsky hole theory, and scaling parameters of pressure, volume, and temperature are obtained. Satisfactory agreement between theory and experiment is found over the entire range of experimental pressures. (C) 1998 John Wiley & Sons, Inc.
Keywords: specific volume; Tait equation; compressibility; scaling parameter; hole theory; THEORETICAL CONSIDERATIONS; AMORPHOUS POLYMERS; PRESSURE; TEMPERATURE; POLYETHYLENE; PARAMETERS; LIQUID